Efektivitas Manual Visceral Physiotherapy terhadap Regulasi Tekanan Darah pada Lansia dengan Hipertensi Esensial: Sebuah Studi Pra-Eksperimental: Effectiveness of Manual Visceral Physiotherapy on Blood Pressure Regulation in Elderly Patients with Essential Hypertension: A Pre-Experimental Clinical Study - Achmad, Arisandy; Cahya, Wahyuni Dwi; Astuti, Lilies Anggarwati (Jurnal Sains dan Kesehatan, 2025)
Essential hypertension is a leading cause of global morbidity and mortality, especially in the elderly population. Non-pharmacological interventions like Manual Visceral Physiotherapy (MVP) are being developed as an alternative approach to help reduce blood pressure without pharmacological side effects. This study aims to determine the effectiveness of MVP on changes in systolic and diastolic blood pressure in elderly patients with essential hypertension. This study used a pre-experimental design with a one-group pretest-posttest approach on 11 respondents aged ?46 years who underwent 12 sessions of MVP over 4 weeks. Blood pressure was measured before and after the intervention using a sphygmomanometer and analyzed with the Wilcoxon Signed Rank Test. The results showed that the average systolic blood pressure decreased from 162 mmHg to 129 mmHg, and diastolic from 96 mmHg to 81 mmHg, with a p-value = 0.003 indicating a significant decrease. It can be concluded that MVP is effective in reducing blood pressure in elderly patients with essential hypertension and has the potential to be used as a complementary therapy in physiotherapy practice. Keywords:          Hypertension, Visceral Physiotherapy, Elderly   Abstrak Hipertensi esensial merupakan penyebab utama morbiditas dan mortalitas global, khususnya pada lansia. Manual Visceral Physiotherapy (MVP) dikembangkan sebagai intervensi non-farmakologis untuk menurunkan tekanan darah tanpa efek samping obat. Penelitian ini bertujuan mengetahui efektivitas MVP terhadap perubahan tekanan darah sistolik dan diastolik pada lansia dengan hipertensi esensial. Desain penelitian menggunakan pra-eksperimen dengan one group pretest-posttest pada 11 responden berusia ?46 tahun yang menjalani 12 sesi MVP selama 4 minggu. Tekanan darah diukur sebelum dan sesudah intervensi, lalu dianalisis dengan uji Wilcoxon Signed Rank. Hasil menunjukkan penurunan rata-rata tekanan darah sistolik dari 162 mmHg menjadi 129 mmHg dan diastolik dari 96 mmHg menjadi 81 mmHg, dengan nilai p=0,003 yang menunjukkan signifikansi statistik. Disimpulkan bahwa MVP efektif menurunkan tekanan darah dan berpotensi sebagai terapi komplementer dalam fisioterapi. Kata Kunci:         Hipertensi, Fisioterapi Viseral, Lansia